Business Feasibility of Agroforestry in Sileutu Village, Sibaganding Nagori, Simalungun Regency - Rozalina Rozalina; Sarintan E Damanik; Rainhard Pandiangan (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to analyze the feasibility of agroforestry practices in Sileutu Village, Sibaganding Sub-village, Girsang Sipangan Bolon Subdistrict, Simalungun Regency, using observation and interviews. The total income from coffee agroforestry in Sileutu Nagori Sibaganding Village, Girsang Sipangan Bolon Subdistrict, Simalungun Regency, averaged IDR 1,498,940 per month and IDR 17,987,280 per year. Based on the R/C ratio analysis, which yielded a value of 9.20, it can be concluded that the coffee agroforestry business in Sileutu Village, Sibaganding Nagori, Girsang Sipangan Bolon Subdistrict, Simalungun Regency, is profitable and viable for further development